Research on the formation of Pseudomonas aeruginosa biofilms as a factor in the development of antibiotic resistance in fatal pneumonias - Bondarenko, Olha; Mishyna, Maryna; Chetta, Alfredo; Malanchuk, Svitlana; Mishyn, Mykhailo; Mozgova, Yuliya; Marchenko, Iryna; Pisi, Roberta; Frizzelli, Annalisa; Kot, Yurii (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Antibiotic resistance of community-acquired pneumonias pathogens and emergence of multiresistant bacteria is a problem of global importance. Therefore, determining the ability to form biofilms will provide an opportunity to develop new ways to overcome bacterial resistance to antimicrobial drugs. Thus, the purpose of this study was to determine Pseudomonas aeruginosa isolates antibiotic resistance and to study the architecture of its biofilms. Methods: Study of the causes of fatal cases of secondary pneumonia against with underlying gunshot trauma for the period from 2022 to 2023. Isolation and identification of pure culture was provided using Micro-la-test kits. The sensitivity to antimicrobial drugs was studied using «SENSILAtest G-I, G-II» and Kirby-Bauer Disk Diffusion Susceptibility Test. To form bioﬁlms bacteria was grown on the surface of coverslips in the 35 mm Petri dishes for 24 h. Biofilm formation was assessed by laser scanning confocal microscopy and scanning electron microscopy.Results: Examination of biological samples revealed 22 strains of microorganisms. Gram-negative microorganisms predominated among pathogens (63.6 %), and Pseudomonas aeruginosa isolates were 50 %. Determining of the sensitivity established that panresistantance to antimicrobial drugs took place in 71.4 % of cases (5 strains), and polyresistantance was found in 28.6 % of cases (2 strains). Conclusions: the study of structural and functional features of biofilms formation showed that biofilms were  formed according to classical stages. Dense biofilms determined the phenotypic variability of Pseudomonas aeruginosa with the development of antibiotic resistance to antimicrobial drugs, that is a barrier for the use of antimicrobial therapy.